Quantitative Perfusion Analysis of the Rectum Using Golden-Angle Radial Sparse Parallel Magnetic Resonance Imaging: Initial Experience and Comparison to Time-Resolved Angiography With Interleaved Stochastic Trajectories. Issue 12 (December 2017) - Attenberger, Ulrike I.; Liu, Jing; Riffel, Philipp; Budjan, Johannes; Grimm, Robert; Block, Kai T.; Schoenberg, Stefan O.; Wang, Xiaoying; Hausmann, Daniel
Abstract : Objectives: Purpose of this study was to compare the quality of perfusion maps obtained from prototypical free-breathing magnetic resonance imaging (MRI) with continuous golden-angle radial sampling and iterative reconstruction (GRASP) to conventional acquisition using time-resolved angiography with interleaved stochastic trajectories (TWIST) in patients with rectal cancer. Material and Methods: Forty cases were included for retrospective analysis. Twenty of the patients received routine multiparametric MRI at 3 T for rectal cancer staging, including perfusion measurement with GRASP or TWIST (10 patients for each technique, including 5 prechemoradiation and 5 postchemoradiation). Twenty patients without history of rectal disease served as control group (10 GRASP, 10 TWIST). GRASP images were reconstructed at temporal resolution of 3.45 seconds (21 spokes/frame). A voxel-by-voxel deconvolution approach was used to determine rectal plasma flow (mL/100 mL per minute). Regions of interest were placed at 3 levels within the tumor and normal rectum (lower, middle, and upper part). The quality of morphologic images, perfusion maps, and arterial input function were scored by 2 blinded radiologists. Independent t tests were applied. Results: Three patients of the TWIST control group had to be excluded due to technical failure of the sequence. Significantly higher scores for the perfusion maps and arterial input functions (total cohort) were obtained using GRASP ( P < 0.05). Artifacts in the perfusion maps were rated significantly lower than for TWIST ( P < 0.05). In the healthy rectum cohort, the average plasma flow of normal rectal wall was 31.78 ± 7.39 mL/100 mL per minute with GRASP, compared with 77.62 ± 34.08 mL/100 mL per minute with TWIST, indicating much lower variance for GRASP. Plasma flow values obtained with both methods enabled distinguishing between normal rectal wall and rectal cancer, both before and after chemoradiation. Morphologic image quality was generally higher with GRASP ( P < 0.01). Conclusions: GRASP perfusion imaging can distinguish between normal rectum and rectal cancers with higher image quality and less variance than TWIST. Additional morphologic assessment with high spatial resolution from the GRASP acquisition may increase the accuracy and diagnostic confidence of the examination.